2020
DOI: 10.3389/fmicb.2020.02003
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Discovered Humic-Reducing Bacterium, Pseudomonas geniculata PQ01, Isolated From Paddy Soil Promotes Paraquat Anaerobic Transformation

Abstract: Due to toxicity and persistence of paraquat (a widely used herbicide), eco-friendly remediation approaches to its contamination and effective antidotes to its poisoning have been highly desired and raised increasing concerns. Paraquat degradation was lesser in aerobic soil in comparison with anaerobic soil, and humic-reducing microorganisms (HRMs) play a key role in paraquat anaerobic transformation process. However, the degradation pathways and related mechanisms remain poorly understood. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Similarly, excessive water content can lead to anoxic conditions that can affect microbial work as well. The results showed that anoxic conditions have an increased degradation process of pesticides as determined for HCH and DDT [63]. Temperature and pH are also important factors influencing the remediation or degradation process [9].…”
Section: Bioremediationmentioning
confidence: 93%
“…Similarly, excessive water content can lead to anoxic conditions that can affect microbial work as well. The results showed that anoxic conditions have an increased degradation process of pesticides as determined for HCH and DDT [63]. Temperature and pH are also important factors influencing the remediation or degradation process [9].…”
Section: Bioremediationmentioning
confidence: 93%
“…P. geniculata, a recognized species, opens avenues for understanding its specific ecological roles and contributions to the overall microbial community dynamics (Wu et al, 2022). The prevalence of unidentified species suggests the potential for uncovering novel microbial diversity within Tanjung Mas seawater, highlighting the importance of advanced sequencing techniques for future taxonomic exploration (Wu et al, 2020). Future studies also need to incorporate multiple samples over time, allowing for a more thorough examination of microbial community dynamics.…”
Section: Genus and Species-level Richnessmentioning
confidence: 99%
“…Different genera of bacteria capable of Paraquat biodegradation were identified in many other studies. These include genera such as Sphingomicrobium marinum, Ferrovibrio xuzhouensis, Azospirillum lipoferum, Altererythrobacterinangensis, Xanthobacter.autotrophicus, Pseudomonas geniculata and Azospirillum amazonense (21,22). The diversity of Paraquat degrading bacteria may be attributed to the differences in the environmental conditions where these organisms were isolated as each organism may be well adapted and suited to a particular environmental condition.…”
Section: Identification Of Paraquat-degrading Bacteriamentioning
confidence: 99%